A note on «Himno a la juventud»: some pictorical references (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2025)
Jaime Gil de Biedma stated in an interview that behind the long descriptive passage of «Himno a la juventud» there were some extremely famous pictorial images: Rubens’ Ganymede, as well as Botticelli’s Birth of Venus and Spring. Our purpose has been to investigate to what extent this relationship exists, tracing the most relevant interpretations of those works that, when «Himno a la juventud» was composed, were prestigious or that could have interested the poet the most when composing his text. Thus, we have echoed the contributions of some great names in the history of art such as A. Warburg, E. H. Gombrich, E. Wind or E. Panofsky and how they could have influenced Jaime Gil de Biedma while writing «Himno a la juventud».
Keywords: «Himno a la juventud»; The Rape of Ganymede, The Birth of Venus; Spring.